Cost-effectiveness of a community-based intervention for reducing the transmission of Schistosoma haematobium and HIV in Africa. - Ndeffo Mbah, Martial L; Kjetland, Eyrun F; Atkins, Katherine E; Poolman, Eric M; Orenstein, Evan W; Meyers, Lauren Ancel; Townsend, Jeffrey P; Galvani, Alison P (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Epidemiological studies from sub-Saharan Africa show that genital infection with Schistosoma hematobium may increase the risk for HIV infection in young women. Therefore, preventing schistosomiasis has the potential to reduce HIV transmission in sub-Saharan Africa. We developed a transmission model of female genital schistosomiasis and HIV infections that we fit to epidemiological data of HIV and female genital schistosomiasis prevalence and coinfection in rural Zimbabwe. We used the model to evaluate the cost-effectiveness of a multifaceted community-based intervention for preventing schistosomiasis and, consequently, HIV infections in rural Zimbabwe, from the perspective of a health payer. The community-based intervention combined provision of clean water, sanitation, and health education (WSH) with administration of praziquantel to school-aged children. Considering variation in efficacy between 10% and 70% of WSH for reducing S. hematobium transmission, our model predicted that community-based intervention is likely to be cost-effective in Zimbabwe at an aggregated WSH cost corresponding to US $725-$1,000 per individual over a 20-y intervention period. These costs compare favorably with empirical measures of WSH provision in developing countries, indicating that integrated community-based intervention for reducing the transmission of S. hematobium is an economically attractive strategy for reducing schistosomiasis and HIV transmission in sub-Saharan Africa that would have a powerful impact on averting infections and saving lives.
Keywords: Animals; Child; Communicable Disease Control; Community Health Services; Cost-Benefit Analysis; Female; Health Care Costs; Health Promotion; HIV Infections; Humans; Infectious Disease Medicine; Male; Models, Economic; Outcome Assessment (Health Care); Prevalence; Probability; Schistosomiasis; Zimbabwe